Serbian Army and the risk management of accidents involving dangerous substances - Rutić, Srđan Z.; Inđić, Dejan R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The article describes the role and the place of the Serbian Army in the risk management of accidents involving dangerous substances as well as the   activities such as taking measures for controling chemical hazards, protection from chemical contamination and elimination of consequences. A method of plan drafting for the risk management in garrisons in case of accidents involving  dangerous substances has been presented. Taking into account all the elements of the assessment of potential accidents involving  dangerous substances and their mutual influence serves as a basis for planing and organising preparedness of units and institutions of the Army for accidents involving  dangerous substances. The Serbian Army has a significant place and role in dealing with accidents with hazardous materials. Introduction Accidents involving  dangerous substances are possible at all times and everywhere, especially in urban areas with chemical plants, warehouses for hazardous chemical materials and heavy traffic and transport of hazardous and toxic substances. The consequences of accidents involving  dangerous substances can pose a threat to the Serbian Army as well as to other structures of the society, which requires  organizing protective safety mesures. In certain cases, the Serbian Army can be a major carrier of measures addressing accidents, regardless of whether it is directly affected or not. The chemical accident risk managemnet in the Army  is a part of the overall risk management in the Army. Preventive actions, early warning,alert of units and emergency measures of chemical protection are taken, as well as first aid, mitigation and elimination of consequences, thus creating favorable and safe conditions for life and work of the units and institutions of the Army in case of chemical accidents. The chemical accident risk management includes (Rutić, 2009): - chemical accident control; - protection against chemical contamination; - elimination of the resulting consequences. The chemical accident control plan for peacetime conditions is made at the level of garrisons (airports, ports). Garrison (airport, port) commands are responsible for such a plan, notably the following personnel: - coordination team for the risk management of peacetime nuclear and chemical accidents - other professional bodies in garrison commands and units, and - relevant competent and professional bodies of public authorities and enterprises engaged in the production, storage or transportation of dangerous goods. The plan includes all the essential elements important for the organization of activities that create conditions for life and work of units (institutions) in case of an accident. The Plan is based on "Guidelines for the risk management in the Army of Serbia in case of nuclear and chemical accidents in peace", published by SAF, 2008  and “The regulations on the methodology for hazard assessment from chemical accidents and environmental pollution , measures of preparedness and remediation of consequences“ The Official Gazette of the Republic of Serbia No. 60/1994). The chemical accident management plan generally includes: - chemical accident hazard assessment, - assessment conclusion, and - order for the organization of  risk management activities.Besides these basic documents, other relevant documents are collected  to ensure a better organization of chemical accident risk management (a map with assessment elements, a task force engagement plan, guidelines for team activities, etc.). The Plan is based on a chemical accident risk assessment,  the quality of which affects the quality of the overall risk management of chemical accidents in peacetime. Risk assessment is carried out continuously -  types, characteristics, quantities and locations of potential sources of chemical hazards are continously monitored, updated and incorporated in the written form into the Risk Management Plan. A software package, ’’HeSPRO’’, was created with the intention of combining the assessment and forecasting of the effects of dangerous substances both in peacetime and during the use of highly toxic substances (Lukovic, et al., 2004). Conclusion Taking into account all the elements of the assessment of potential accidents involving dangerous substances and their mutual influence serves as a basis for planing and organising the risk management of accidents involving dangerous substances at the level of units and institutions of the Army. The Serbian Army has a significant place and role in the risk management of accidents with hazardous materials. The organization of emergency responses to accidents involving hazardous materials, as one of priority tasks, is an extremely complex activity that requires fully qualified profesionalsable to effectively respond to an accident with hazardous materials in accordance with the prepared Plan of the garrison level risk management of accidents with hazardous materials. The organization of risk management in these types of emergencies is an extremely complex activity requiring a systematic and multidisciplinary approach. The ultimate goal of allefforts in addressing this problem is to minimize the risk in all phases of managing accident situations.
Keywords: accidents involving hazardous substances; CBRN; hazardous materials; assessment; toxic chemicals